Analysis Of Stock Market Reaction In Malaysia During Covid-19 Pandemic Via Arima - Nor Aziyatul Izni Mohd Rosli; Sarah ‘Atifah Saruchi; Puvarasan Ulaganathan4; Gurpreet Singh Awtar Singh4; Nurul Azhani Yunus; Nur Ilyana Ismarau Tajuddin (Universiti Malaysia Pahang Al-Sultan Abdullah, 2024)
Journal of Mechatronics and Intelligent Manufacturing (Mekatronika) Volume 5 Issue 1 Page (1-12)